The Influence of Brand Image and Quality of E-Channel Product Services on Transaction Interest and Customer Satisfaction - Wardatul Jannah, Lulu; Wirastomo, Handoyo (UIN Mataram, 2024)
This research aims to identify the influence of brand image and E-Channel product service quality on transaction interest and customer satisfaction. Using a quantitative survey approach, the study involves 98 respondents, equally divided by gender. A Likert scale questionnaire with 30 questions was used.For variables X1, X2, and Y1, regression analysis shows an R value of 0.870 and an R Square value of 0.757, meaning 75.7% of the variance is explained by the model. ANOVA results reveal an F value of 148.038 with a significance level below 0.001. The quality of E-Channel product services has a stronger influence (Beta = 0.677) than brand image (Beta = 0.218).For variables X1, X2, and Y2, the model summary shows an R value of 0.914 and an R Square value of 0.836, explaining 83.6% of the variance. ANOVA results show an F value of 241.910 with a significance level below 0.001. The quality of E-Channel product services has a stronger impact (Beta = 0.523) compared to brand image (Beta = 0.428).The study concludes that improving E-Channel product service quality and brand image enhances transaction interest and customer satisfaction.This study is essential to provide a deeper understanding of the factors influencing customer interest and satisfaction in using E-Channel services. The findings indicate that improving the quality of E-Channel service products and brand image can enhance customer transaction interest and satisfaction, which has significant implications for marketing strategies and the enhancement of banking services.